Inovasi Alat Deteksi Sederhana untuk Arus Induksi Menggunakan Prinsip Gaya Lorentz Berdasarkan Transistor C-945 - Dika Nopriyanto; Arini Rosa Sinensis; Siti Anisatur Rofiqah (UNIVERSITAS INDRAPRASTA PGRI, 2023)
Along with the development of technology, electrical energy is much needed in everyday life, not only as a light that illuminates the streets of the city at night but also a driver of economic, social and cultural strength. The making of this tool aims to find out the location of the breaking point (not flowing induction current) which is not electrified on the conductor/cable by using an LED lamp and an active buzzer as a pointer indicator. By making this tool, it is expected to facilitate the work and installation of other electrical installations and improve safety at work. By using qualitative and quantitative methods characterized by the success of making this tool. The next step is the measurement of the noise level generated by the active buzzer and presented in the form of (x) and (y) tables, meanwhile (x) and (y) comparison graphs to fulfill the quantitative method. The attachment of the principles of electrical physics to each other is what can be utilized to make other simple tools.